Adverse drug reactions associated with sunitinib therapy: characteristics and risk factors - Mugoša, Snežana; Džamić, Zoran; Šahman-Zaimović, Majda; Lukovac-Janjić, Nevenka (Vojnosanitetski pregled, 2021)
Background/Aim. Kidney tumors account for 2–3% of all tumors. Renal cell carcinoma (RCC) is the tenth most common malignancy. Sunitinib is used as the first treatment line in patients with a good and intermediate prognosis. The aim of this study was to analyze the risk factors, frequency, and adverse drug reactions (ADRs) of sunitinib in patients with metastatic RCC. Methods. The retrospective study included 170 patients treated at the Clinic for Oncology of the Clinical Center of Montenegro, Urology Clinic of the Clinical Center of Serbia, and Clinic for Oncology of the Clinical Center Niš. As a data source, we used patient medical histories and/or electronic patient records. ADRs were characterized by using Rawlins and Thompson classification. Each ADRs severity was assessed in accordance with the World Health Organization criteria. Causality was assessed using the Naranjo probability scale. Results. ADRs of sunitinib occurred in 152 (89.4%) patients. ADRs were 89% type A and 11% type C. Disorders of the blood and lymphatic system, gastrointestinal disorders, and disorders of the skin and subcutaneous tissue were the most common manifestations of ADRs of sunitinib. Causality assessment was most commonly classified as certain (60%). Serious ADRs occurred in 4.5% of patients. Most patients recovered without consequences. The most common manifestations of ADRs were: leukopenia, hypothyroidism, thrombocytopenia, diarrhea, stomatitis, asthenia, and hypertension. All ADRs were expected. The number of concomitant medications and the duration of therapy proved to be the most significant risk factors for ADR to sunitinib. Conclusion. Our study shows that the incidence of ADRs of sunitinib in patients with kidney cancer is high. The ADRs were mostly moderate and mild in intensity and occurred as a consequence of the pharmacological action of the drug. It is necessary to conduct continuous education of medical oncologists in the field of monitoring safe drug use, as well as patients on sunitinib therapy, in order to improve their awareness of the sunitinib ADRs and the risk factors that lead to them, with the aim of reducing their frequency.